2002
DOI: 10.1093/molehr/8.8.750
|View full text |Cite
|
Sign up to set email alerts
|

Possible role for Ca2+ calmodulin-dependent protein kinase II as an effector of the fertilization Ca2+ signal in mouse oocyte activation

Abstract: The present study shows that Ca(2+) calmodulin-dependent protein kinase II (CaM kinase II) is physiologically activated in fertilized mouse oocytes and is involved in the Ca(2+) response pathways that link the fertilization Ca(2+) signal to meiosis resumption and cortical granule (CG) exocytosis. After 10 min of insemination, CaM kinase II activity increased transiently, then peaked at 1 h and remained elevated 30 min later when most of the oocytes had completed the emission of the second polar body. In contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
4

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 61 publications
1
47
0
4
Order By: Relevance
“…CaMKII inhibitors inhibit cell cycle progression in both parthenogenetically activated and fertilized mouse eggs (12,25,26). Conversely, expression of a truncated, constitutively active form of CaMKIIα triggers cell cycle resumption (27), reduction in MAPK and MPF activities, PN formation, and maternal mRNA recruitment, all in the absence of Ca 2+ oscillations (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CaMKII inhibitors inhibit cell cycle progression in both parthenogenetically activated and fertilized mouse eggs (12,25,26). Conversely, expression of a truncated, constitutively active form of CaMKIIα triggers cell cycle resumption (27), reduction in MAPK and MPF activities, PN formation, and maternal mRNA recruitment, all in the absence of Ca 2+ oscillations (28).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is well established that a rise in [Ca 2+ ] i is required for CG release, the downstream Ca 2+ -dependent mediators of this signal are still poorly defined. Pharmacological inhibitors of CaMKII block CG exocytosis in both fertilized and ethanol-activated mouse eggs (26). Nevertheless, expressing an artificially truncated, constitutively active form of CaMKIIα in mouse eggs results in ab- normal CG exocytosis, even though other EEA are normal (28).…”
Section: Discussionmentioning
confidence: 99%
“…Calmodulin can regulate the activity of many other proteins at fertilization, including calmodulin-dependent kinase II (CaM kinase II). CaM kinase II activity undergoes oscillations following fertilization in mouse eggs (Markoulaki et al, 2003(Markoulaki et al, , 2004, and this activity is important for cortical granule exocytosis and progression through the cell cycle, based on evidence that shows inhibitors of calmodulin or CaM kinase II block both latter processes (Abbott and Ducibella, 2001;Tatone et al, 2002). Notably, CaM kinase II has the ability to regulate NOS function (Michel and Feron, 1997;Schneider et al, 2003).…”
Section: The Role Of Nitric Oxide and Cyclic Adp Ribose During Fertilmentioning
confidence: 99%
“…A role had recently been suggested for proteins, such as CaMKII and calmodulin, in mediating the signal required for the resumption of meiosis (Tatone et al 2002, Markoulaki et al 2003. In a study exploring the role of CaMKII during activation of mouse eggs, Markoulaki et al (2004) demonstrated that CaMKII antagonist inhibits cell-cycle progression in fertilized, but not cycloheximide-treated, eggs.…”
Section: Ionomycinmentioning
confidence: 99%
“…Little is known regarding the cellular pathways by which calcium exerts its signal during egg activation. Recently, a role had been suggested for proteins such as Ca 2þ /calmodulin-dependent protein kinase II (CaMKII) and calmodulin in mediating the signal required for resumption of meiosis (Tatone et al 2002, Markoulaki et al 2003.…”
Section: Introductionmentioning
confidence: 99%